Accelerated sample preparation and formation of astragaloside IV in Astragali Radix. (April 2014) - Monschein, Marlene; Ardjomand-Woelkart, Karin; Rieder, Johann; Wolf, Isabella; Heydel, Barbara; Kunert, Olaf; Heuberger, Heidi; Bauer, Rudolf
Abstract Context: Astragali Radix (Huangqi; Astragalus mongholicus BUNGE, Fabaceae) is used in herbal medicinal products as well as in many food supplements. In traditional Chinese medicine, the roots are used for its Qi tonifying, immunostimulant, cardioprotective, hepatoprotective and hypoglycemic effects. Objective: Astragaloside IV (AGS-IV), a cycloartane-type triterpene glycoside is used as a marker compound for the quality control of Astragali Radix in various pharmacopoeias. Materials and methods: In this study, we analyzed the content of AGS-IV and other astragalosides in various commercial samples of Huangqi by reversed-phase HPLC using evaporative light scattering detection. Results: The analyses revealed that AGS-IV is formed during sample preparation from acylated astragalosides like astragaloside I and astragaloside II, when using the assay method of the European Pharmacopoeia. Discussion and conclusion: For consistent assay results, the extraction methods of the pharmacopoeias should be re-evaluated and optimized. Alternatively, the hydrolysis by ammonia could be omitted and the genuine compounds like astragaloside I, II and malonyl-AGS-I could be considered for the quality control of Astragali Radix.